Photocatalyzed Enantioselective Functionalization of C(sp3)–H Bonds - Xu, Guo-Qiang; Wang, Wei David; Xu, Peng-Fei (Journal of the American Chemical Society, 2024)
Owing to its diverse activation processes including single-electron transfer (SET) and hydrogen-atom transfer (HAT), visible-light photocatalysis has emerged as a sustainable and efficient platform for organic synthesis. These processes provide a powerful avenue for the direct functionalization of C(sp3)–H bonds under mild conditions. Over the past decade, there have been remarkable advances in the enantioselective functionalization of the C(sp3)–H bond via photocatalysis combined with conventional asymmetric catalysis. Herein, we summarize the advances in asymmetric C(sp3)–H functionalization involving visible-light photocatalysis and discuss two main pathways in this emerging field: (a) SET-driven carbocation intermediates are followed by stereospecific nucleophile attacks; and (b) photodriven alkyl radical intermediates are further enantioselectively captured by (i) chiral π-SOMOphile reagents, (ii) stereoselective transition-metal complexes, and (iii) another distinct stereoscopic radical species. We aim to summarize key advances in reaction design, catalyst development, and mechanistic understanding, to provide new insights into this rapidly evolving area of research.